Quantitative Myasthenia Gravis Score: a Brazilian multicenter study for translation, cultural adaptation and validation - Oliveira, Ezequiel Fernandes; Valério, Berenice Cataldo Oliveira; Cavalcante, Valéria; Urbano, Jessica Julioti; Silva, Anderson Soares; Polaro, Melissa Nunes; Nacif, Sergio Roberto; Oliveira, Claudia Santos; Resende, Maria Bernadete Dutra; Oliveira, Acary Souza Bulle; Oliveira, Luis Vicente Franco (Arquivos de Neuro-Psiquiatria, 2017)
To perform the translation, cross-cultural adaptation and validation of the Quantitative Myasthenia Gravis Score (QMGS) to Brazilian Portuguese in accordance with international ethical standards.The following steps were taken: (1) implementation of the translation protocol and transcultural adaptation, (2) validation of the adapted content, and (3) assessment of reliability. To check intra- and inter-observer reproducibility, each patient underwent two interviews with interviewer-A and one with B. The QMGS was compared to the Myasthenia Gravis Composite Scale and Myasthenia-specific Quality of Life Questionnaire.Our study group consisted of 30 patients, with a mean age of 47.6±11.4 years and a mean duration of illness of 11.33±8.49 years. Correlation between the QMGS and MGC was very strong (r = 0.928; p < 0.001) and substantial between the QMGS and MG-QOL 15 (r = 0.737; p < 0.001).The Brazilian Portuguese translation, and validation of the QMGS was successfully performed.
Keywords: myasthenia gravis; cross-cultural comparison; translations; validation studies